UTILIZATION OF WIND ENERGY CONVERSION SYSTEM IN INDONESIA - Saputro, Soeripno Marto (185P -3466)
Wind energy is one of the alternative resources that has been developed in Indonesia to support the National Renewable Energy Program. Many areas in Indonesia, have annual wind speed between 2.5 to 5 meter per second. It is enough to support the rural electrification program by applying a small WECS for home lighting, battery charging, cold storage, telecommunication etc.Certain areas in East Nusa Tenggara, West Nusa Tenggara, South Sulawesi and southern part of Java have annual wind speed more than 5 m/s. This gives a possibility to implement a medium to a large size WECS for electric generation. Various WECS of up to 10 kW have been developed. Field test on several villages are progressing. This paper also describes a prospect of WECS utilization, benefit and a possible barrier of WECS implementation and recommendation.